7.1 ANALYSIS OF METHODS OF CALCULATION OF PERIODICITY OF DEFECTOSCOPIC DIAGNOSTICS OF RAIL CONDITION IN THE TRACK - Begmatov Pardaboy Abdurakhimovich, Associate Professor Eshonov Farhod Faizullaevich, Senior Lecturer (Innovative technologies in construction Scientific Journal, 2024)
The article deals with defectoscopic diagnostics of rail condition on high-speed sections of railroad track. Key words: rail, joint less track, rail defects, rail stresses. To ensure the safety of train traffic it is necessary not only to improve the system of defectoscopic diagnostics of rails in the track, but also to implement a set of measures to reduce their damageability by defects. Improvement of quality of work of defectoscopic diagnostics means, for example, diagnostics is realized at the expense of selection of optimal for a given track section periodicity of defectoscopic diagnostics of rails condition on the basis of studied regularities of intensity of defects development in rails, increase of resolution of defectoscopic diagnostics means. Transverse cracks in the head of defect rails represent a great danger due to the probability of brittle failure of rails in the track, as at significant development of the crack the strength of rails is sharply reduced. It is possible to determine the required periodicity of defectoscopic diagnostics of rails condition in the track at known crack growth rate in different operating conditions for each type of means of defectoscopic diagnostics, based on its minimum resolving ability to detect defects. The complex of works on reduction of rails damageability by surface and internal defects includes measures: on creation of high straightness of rolling surface of the head of new rails and preventive - on removal of various irregularities and damages of rails. Realization of periodic grinding of rails on the way allows to remove the damage layer of metal on the head surface, to separate the time of appearance and intensity of subsequent development of various defects, thereby increasing the reliability of rails against brittle fracture. Besides, after high quality grinding of rails the conditions of detection by means of defectoscopic diagnostics of dangerous internal cracks are improved due to significant reduction of interference from surface defects in the form of micro and macro cracks, flaking, scrapes removed during grinding, as well as reduction of depth of internal cracks from the rolling surface, which is especially favorable for increasing the efficiency of work. It is obvious that periodicity of defectoscopic diagnostics of track cannot be constant in time once and for all established value, frequency of defectoscopic diagnostics increases with the growth of operating tonnage, as the probability of defective rails appearance increases. Consideration of specific operating conditions is based on standards and experience of managers and engineering and technical workers of distances and track services, as well as on existing technical capabilities and availability of defectoscopic diagnostics means.